Sociocultural determinants of e-cigarette use among generation Z as a lifestyle - Widyanty, Winda (Priviet Social Sciences Journal, 2024)
The behavior of using electronic cigarettes has become a major concern among generation Z in Indonesia because its prevalence continues to increase. The aim of this research is to describe the socio-cultural determinants that influence the behavior of using e-cigarettes in generation Z. Through a literature review, this article presents an overview of the socio-cultural factors that influence the use of e-cigarettes, as well as the implications of this behavior for public health. For this purpose, perceptions and reasons for using electronic cigarettes, which are reviewed from a socio-cultural perspective, are discussed systematically in generation Z. PUBMED and Scopus are used to search for articles that fit the predetermined theme and sub-theme categories, namely from social factors, including peer influence. and family, the influence of media and advertising. Meanwhile, cultural factors include social norms and the popularity of innovative products.